Comparison of thermal shock behaviors between plasma-sprayed nanostructured and conventional zirconia thermal barrier coatings - 刘纯波 张志民 蒋显亮 刘敏 朱朝辉 (Transactions of Nonferrous Metals Society of China, 2009)
NiCoCrAlTaY bond coat was deposited on pure nickel substrate by low pressure plasma spraying（LPPS）, and ZrO2-8%Y2O3 （mass fraction） nanostructured and ZrO2-7%Y2O3 （mass fraction） conventional thermal barrier coatings（TBCs） were deposited by air plasma spraying（APS）. The thermal shock behaviors of the nanostructured and conventional TBCs were investigated by quenching the coating samples in cold water from 1 150, 1 200 and 1 250 ℃, respectively. Scanning electron microscopy（SEM） was used to examine the microstructures of the samples after thermal shock testing. Energy dispersive analysis of X-ray（EDAX） was used to analyze the interface diffusion behavior of the bond coat elements. X-ray diffraetometry（XRD） was used to analyze the constituent phases of the samples. Experimental results indicate that the nanostructured TBC is superior to the conventional TBC in thermal shock performance. Both the nanostructured and conventional TBCs fail along the bond coat/substrate interface. The constituent phase of the as-sprayed conventional TBC is diffusionless-transformed tetragonal（t＇）. However, the constituent phase of the as-sprayed nanostructured TBC is cubic（c）. There is a difference in the crystal size at the spalled surfaces of the nanostructured and conventional TBCs. The constituent phases of the spalled surfaces are mainly composed of Ni2.88Cr12 and oxides of bond coat elements.